2015
DOI: 10.1038/mp.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chronic stress on the rat brain lipidome

Abstract: Chronic stress is a major risk factor for several human disorders that affect modern societies. The brain is a key target of chronic stress. In fact, there is growing evidence indicating that exposure to stress affects learning and memory, decision making and emotional responses, and may even predispose for pathological processes, such as Alzheimer’s disease (AD) and depression. Lipids are a major constituent of the brain, and specifically signaling lipids have been shown to regulate brain function. Here, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
160
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(179 citation statements)
references
References 54 publications
18
160
0
1
Order By: Relevance
“…; Oliveira et al . ). Here we provide, to our knowledge, first evidence for a role of ASM–Cer in the learning processes involved in coping with the absence of expected reward.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Oliveira et al . ). Here we provide, to our knowledge, first evidence for a role of ASM–Cer in the learning processes involved in coping with the absence of expected reward.…”
Section: Discussionmentioning
confidence: 97%
“…Both components are marked by different behaviors. The ASM-Cer system has been suggested to play an important role in genetically induced and stress-induced depression in rodent models (Gulbins et al 2013;Oliveira et al 2016). Here we provide, to our knowledge, first evidence for a role of ASM-Cer in the learning processes involved in coping with the absence of expected reward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have highlighted an association between MDD and the lipidome (32, 34, 35), indeed it has been previously shown that reductions phosphatidylcholine (and sphingomyelin) concentrations are associated with symptoms of depression (33). However, previous research has not shown whether the lipid alterations observed in MDD are secondary to the manifestation of the illness or its treatment, or whether lipid concentrations are related to the genetic predisposition for depression.…”
Section: Discussionmentioning
confidence: 99%
“…We found a decreased L1 copy number in PFC, but there was no change in other regions due to a mild CUMS given in our study. Previous studies demonstrated that there was the highest extent of changes induced by chronic stress in PFC51. Studies of post-mortem brain and imaging revealed that the volume of prefrontal cortex was decreased in MDD, consistent with a reduction in the size and density of neurons5253.…”
Section: Discussionmentioning
confidence: 61%